2014
DOI: 10.1152/ajpgi.00193.2014
|View full text |Cite
|
Sign up to set email alerts
|

Transforming growth factor-β2 and endotoxin interact to regulate homeostasis via interleukin-8 levels in the immature intestine

Abstract: Nguyen DN, Sangild PT, Østergaard MV, Bering SB, Chatterton DE. Transforming growth factor-␤2 and endotoxin interact to regulate homeostasis via interleukin-8 levels in the immature intestine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 39 publications
3
25
0
Order By: Relevance
“…In addition, TGF-β2 specifically attenuates IL1β-induced inflammatory responses in the immature human intestine via an SMAD6- and ERK-dependent mechanism (56). More recently, it has been observed that TGF-β2 and endotoxin interact to regulate homeostasis via IL8 levels in the immature intestine (57). …”
Section: Discussionmentioning
confidence: 99%
“…In addition, TGF-β2 specifically attenuates IL1β-induced inflammatory responses in the immature human intestine via an SMAD6- and ERK-dependent mechanism (56). More recently, it has been observed that TGF-β2 and endotoxin interact to regulate homeostasis via IL8 levels in the immature intestine (57). …”
Section: Discussionmentioning
confidence: 99%
“…The Th2 cytokines such as IL-4 and IL-13, detected in most of our samples and in higher concentration in colostrum, are anti-inflammatory, down-regulate Toll-like receptor activation in human intestinal epithelial cells (Mueller et al, 2006), and would maintain tolerance during initial bacterial colonization. Similarly, TGF-β1 and TGF-β2 would induce T regulatory cells in mesenteric lymph nodes (Renz et al, 2012) and reduce mucosal levels of inflammatory cytokines (Nguyen et al, 2014; Rautava et al, 2012). …”
Section: Discussionmentioning
confidence: 99%
“…Human milk cytokines like TGF-β2 modulate LPS-induced secretion of pro-inflammatory cytokines (Nguyen et al, 2014) and proliferation and differentiation of lymphocytes, phagocytes, and dendritic cells (Agarwal et al, 2011; Chatterton et al, 2013). In fact, TGF-β family cytokines were detectable in all samples we tested, and at increased concentrations in the mature milk of women delivering VLBW infants, the population with the highest risk of NEC, suggesting highly conserved function and supporting the importance of human milk consumption for premature infants.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations